Menuju Gereja Apostolik Transformatif - Gernaida K. R. Pakpahan; Frans Pantan; Epafras Djohan Handojo (Sekolah Tinggi Teologi Torsina Surakarta, 2021)
Peter Wagner, as an expert on church growth, stated that the Apostolic church is a church that is experiencing rapid growth. This claim is made because many Apostolic churches have been built around the world. The church continued the spirit of the apostles at the time of the early church's birth. However, it is important to conduct an in-depth study regarding the realization in the field; whether a thriving Apostolic church is carrying out God's mission or the personal ambition of a charismatic church leader. This study analyzes how the church which is said to be an Apostolic church runs its organization so that it experiences significant growth. The research method used is descriptive qualitative. The researcher tries to explore the phenomena and data obtained through respondents about the transformative apostolic church that was developed in the ministry of the Indonesian Bethel Church of Gatot Subroto. In conclusion, GBI Gatot Subroto is a transformative apostolic church, because of several things, such as a visionary church, senior pastors or mentor pastors as apostolic leaders, divine authority and the work of the Holy Spirit have an impact, the church as a center for leadership training and discipleship across generations implements apostolic ministry followed by other gifts/services, prioritizing mission, and focusing on the Kingdom of God.AbstrakPeter Wagner, sebagai salah satu ahli pertumbuhan gereja, menyatakan bahwa gereja Apostolik adalah gereja yang mengalami pertumbuhan secara pesat. Klaim ini disampaikan karena banyak-nya terbangun gereja-gereja beraliran Apostolik di seluruh dunia. Gereja tersebut melanjutkan semangat para rasul pada masa lahirnya gereja mula-mula. Namun, penting untuk dilakukan kajian mendalam terkait realisasi di lapangan; apakah gereja Apostolik yang berkembang menja-lankan misi Allah atau ambisi pribadi dari pemimpin gereja yang berkharismatik. Penelitian ini menganalisis bagaimana gereja yang dikatakan sebagai gereja Apostolik menjalankan organisa-sinya, sehingga mengalami pertumbuhan yang signifikan. Metode penelitian yang digunakan adalah kualitatif deskriptif. Peneliti berusaha mengeksplorasi fenomena dan data-data yang diperoleh melalui responden tentang gereja apostolik transformatif yang dikembangkan dalam pelayanan Gereja Bethel Indonesia Gatot Subroto. Kesimpu-lannya, GBI Gatot Subroto adalah gereja apostolik transformatif, karena beberapa hal, seperti: gereja yang visioner, gembala senior atau gembala pembina sebagai pemimpin kerasulan, otoritas Ilahi dan pekerjaan Roh Kudus berdampak, gereja sebagai pusat pelatihan kepemimpinan dan pemuridan lintas generasi, menerap-kan jawatan rasuli diikuti karunia-karunia/jawatan lainnya, memprioritaskan misi, dan berfokus pada Kerajaan Allah.